Low Cost Electro-deposition of Cuprous Oxide P-N Homo-junction Solar Cell - Arith, Faiz; Sharafina, Anis; M. Said, Muzalifah; Idris, M. Idzdihar (Trans Tech Publications, 2014)
Most of the photovoltaic industry uses wafer of single crystal and poly-crystal silicon as a material of their photovoltaic (PV) modules. However, the cost of these modules is high due to the material and processing cost. Cuprous oxides (Cu2O)have several features that suitable for future photovoltaic applications. Cu2O can be prepared with simple methods at very low cost. Cu2O p-n homojunction solar cell is a device that converts sunlight to electrical energy, consists of two similar materials for its p-n junction, which is Cu2O. The p-type and n-type of Cu2O thin films are then fabricated to produce solar cells. Other layers aluminium and glass substrate coated with indium tin oxide (ITO) need to be added as a contact for electrons movement. In this study, p-type Cu2O, n-type Cu2O and p-n junction are prepared in order to become accustomed for solar cell applications. To achieve the optimum deposition conditions, p-n junction solar cell is prepared by two-steps electrochemical deposition process. The result from x-ray diffraction (XRD) shows that the peak is dominated by CuO (1, 1, 1). P-n junction is in between the p-type and n-type of Cu2O layer. Al has the thickness of 427.5nm. The second and the third layer are p and n –type of Cu2O, which have the thickness of 106.9nm and 92.3nm, respectively. Finally the thickness of ITO layer is 131.1nm. An absorption experiment at AM1 light is performed in order to get the I-V curves, and in fact, to study the electrical solar cells p-n homojunction. Based on I-V curve test, the level of energy conversion of cell is 0.00141% with fill factor, FF 0.94813 which proved that Cu2O p-n homojunction solar cell can be fabricated and produced at very low cost and well function.